A control-oriented approach to estimate the injected fuel mass on the basis of the measured in-cylinder pressure in multiple injection diesel engines. (15th November 2015) - Finesso, Roberto; Spessa, Ezio
Highlights: Control-oriented method to estimate injected quantities from in-cylinder pressure. Able to calculate the injected quantities for multiple injection strategies. Based on the inversion of a heat-release predictive model. Low computational time demanding. Abstract: A new control-oriented methodology has been developed to estimate the injected fuel quantities, in real-time, in multiple injection DI diesel engines on the basis of the measured in-cylinder pressure. The method is based on the inversion of a predictive combustion model that was previously developed by the authors, and that is capable of estimating the heat release rate and the in-cylinder pressure on the basis of the injection rate. The model equations have been rewritten in order to derive the injected mass as an output quantity, starting from use of the measured in-cylinder pressure as input. It has been verified that the proposed method is capable of estimating the injected mass of pilot pulses with an uncertainty of the order of ±0.15 mg/cyc, and the total injected mass with an uncertainty of the order of ±0.9 mg/cyc. The main sources of uncertainty are related to the estimation of the in-cylinder heat transfer and of the isentropic coefficient γ  =  cp / cv . The estimation of the actual injected quantities in the combustion chamber can represent a powerful means to diagnose the behavior of the injectors during engine operation, and offers the possibility of monitoring effects, such as injector ageing and injector coking, as well as of allowing an accurate control of the pilot injected quantities to be obtained; the latter are in fact usually characterized by a large dispersion, with negative consequences on the combustion quality and emission formation. The approach is characterized by a very low computational time, and is therefore suitable for control-oriented applications.